Pretreatment of Ligno-cellulosic Biomass for Biofuels and Bioproducts: AE495, 1/2013 - Tong, Zhaohui; Cheng, Nusheng; Pullammanappallil, Pratap (EDIS, 2013)
This 4-page fact sheet discusses bioethanol as a renewable form of energy, explaining the importance of using ligno-cellulosic biomass to produce biofuels. It describes the pretreatment step in producing biofuels and the need for more research into this step so that ligno-cellulosic biofuels can be produced cheaply and efficiently at a commercial scale. Written by Zhaohui Tong, Nusheng Cheng, and Pratap Pullammanappallil, and published by the UF Department of Agricultural and Biological Engineering, January 2013. http://edis.ifas.ufl.edu/ae495